Overspinning a nearly extreme charged black hole via a quantum tunneling process - Matsas, George E. A.; da Silva, Andre R. R. (Amer Physical Soc, 2007)
We examine a nearly extreme macroscopic Reissner-Nordstrom black hole in the context of semiclassical gravity. The absorption rate associated with the quantum tunneling process of scalar particles whereby this black hole can acquire enough angular momentum to violate the weak cosmic-censorship conjecture is shown to be nonzero.